Differential effects of corrective feedback on the ESL learners' accuracy of linguistic form - Asiah, Kassim (2014)
This mixed-method study investigated the extent of focused and unfocused indirect corrective feedback efficacy in improving learners' linguistic accuracy in written work over a period of time. The quantitative inquiry that involved two treatment groups (n = 30 for focused indirect corrections and n = 30 for unfocused indirect corrections) and a control group (n = 30), compared the differential effects of focused indirect with the unfocused indirect corrective feedback on the uptake and retention of the accurate use of subject-verb agreement, prepositions and articles as measured from the pretest, immediate and delayed posttests. The participants in the treatment groups were required to complete two writing tasks of which they received either focused or unfocused corrective feedback, arid were required to complete two sessions of collaborative dialogue for the purpose of revising the written work based on the corrective feedback provided. The qualitative inquiry attempted to identify factors relating to the Language-Related Episodes (LREs) that influenced uptake and retention of the corrective feedback on subject-verb agreement, prepositions and articles in the learners' written work. These LREs were derived from the collaborative dialogue that the participants were required to complete for revision sessions. Selected participants were interviewed one week after the delayed posttest to further explore the factors that may have influenced corrective feedback efficacy on the uptake and retention of the targeted linguistic forms. Guided by Swain's (2005) Output Hypothesis, the LREs and interviews were analysed to identify prevailing influencing factors. The statistical findings revealed that both treatment groups outperformed the control group in the immediate and delayed posttests. However, there was no significant difference between the unfocused and focused corrective feedback groups indicating that both correction types were equally facilitative in increasing accuracy of the three targeted structures over a period of time. The qualitative results revealed six main factors that may have greatly influenced the uptake and retention of the corrective feedback on those targeted forms, which are: learners' subsequent response to the corrective feedback; focus on ungrammatical uses; hypothesising of correct forms uses; post-response reflections; linguistic features and task-related factors. Overall, results suggest that while both focused and unfocused corrective feedback may be facilitative in improving language accuracy, based on the influencing factors identified, learners may benefit more from the unfocused corrective feedback. This implication was proposed with the condition that the feedback provided for the written work can retain learners' interest and focus towards task completion.